(untitled) (World Bulletin of Public Health, 2022)
According to various authors, the prevalence of constipation among the adult population of highly developed countries varies from 4 to 45%, and among children - from 0.7 to 34%. In the UK, according to researchers, 34% of children aged 4 to 7 years suffered from constipation. According to research data published in recent years in the Russian Federation (RF), the incidence of constipation in children is about 25-30%. It is believed that 10 to 25% of children suffer from constipation, but its true prevalence in children is unknown due to the low prevalence of parents in this regard to the doctor.